Suspension culture of Aquilaria beccariana van teigh - Khairunisa, Binti Ab Aziz (Universiti Malaysia Sarawak, UNIMAS, 2013)
Aquilaria beccariana van Teigh (Thymelaceae), is a non timber forest product. The tree is valuable for its fragrant wood. Agarwood which is important for incense, traditional medicine, perfumery and others products. The population of Aquilaria has been reduced drastically due to the indiscriminate collection, over exploitation and lacking of rapid natural regeneration. The population of this tree became declined and the production of gaharu is less compared to highly demand of the user. Thus, in vitro technique was selected because it offer rapid regeneration and conservation of these endangered species and this study, attempts were done to produce callus from Aquilaria sp. Works were done to induce callus from lamina explants on MS solid and MS liquid medium supplemented with different combination of hormone (2,4-D, picloram and NAA) and varied concentration of sucrose (20-50 g/L). The callus culture was successfully established in MS solid media supplemented with combination of 2.0 mg/L 2,4-D plus 0.5 mg/L BAP. While in MS liquid medium, the suspension culture successfully established in combination of 3 mg/L NAA plus 0.5 mg/L BAP by obtaining highest frequency of fresh weight (2.09g). Thus, 40 g /L found to be the best sucrose concentration with (1.95 g ) of fresh weight. While, combination of 0.25 mg/L picloram with 2.0 mg/L 2,4-D and 0.5 mg/L BAP gave high frequency of fresh weight ( 1.06 g) in Picloram effect. Suspension culture of callus gave friable and compact in texture and globular and irregular in shape.